Fault diagnosis of a water for injection system using enhanced structural isolation - Laursen, Morten; Blanke, Mogens; Düştegör, Dilek (Zielona Góra: Uniwersytet Zielonogórski)
A water for injection system supplies chilled sterile water as a solvent for pharmaceutical products. There are ultimate requirements for the quality of the sterile water, and the consequence of a fault in temperature or in flow control within the process may cause a loss of one or more batches of the production. Early diagnosis of faults is hence of considerable interest for this process.
Keywords: structural analysis; fault isolation; fault diagnosis; matching